2004
DOI: 10.1097/01.sap.0000095437.43805.d1
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction With Gluteal Artery Perforator (GAP) Flaps

Abstract: Fujino was the first to introduce gluteal tissue as a free flap for breast reconstruction. The use of the musculocutaneous flap from the buttock in breast reconstruction has been championed by Shaw. Despite the initial enthusiasm for this area as a donor site, few other large series exist on the subject. Two decades of experience with this region as a donor site led to recognition of advantages and drawbacks. Furthermore, use of both the superior and inferior gluteal musculocutaneous flap was associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
4
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 27 publications
(36 reference statements)
1
104
4
9
Order By: Relevance
“…Some reports on the IGAP flap have presented outcomes on the donor site, but none have quantitative or objective data. Dysesthesia on the posterior thigh and contour deformity were recurrent complaints of patients in these studies (5,7,9,12,16).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports on the IGAP flap have presented outcomes on the donor site, but none have quantitative or objective data. Dysesthesia on the posterior thigh and contour deformity were recurrent complaints of patients in these studies (5,7,9,12,16).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 142 GAP flaps, the superior-GAP flap was found to have significant advantages over the inferior-GAP flap. Guerra et al reported low morbidity, 98% flap survival, good cosmetic results and high levels of patient satisfaction [50].…”
Section: Autologous Flapsmentioning
confidence: 99%
“…Perforating vessels are found off of the superior branch of the superior gluteal artery. 27,28 Pre-operatively CTA or MRA has greatly impacted planning of this procedure.…”
Section: Anatomymentioning
confidence: 99%